21st Century Skills and Information Literacy in Indonesian Language and Literature Education Study Program - Ida Bagus Rai Putra; Mukhamdanah; Ida Ayu Putu Aridawati; I Wayan Sudiartha; Ni Putu Parmini (Mimbar Ilmu, 2023)
21st Century Skills and Information Literacy are very important to know about their development in the lecture process in tertiary institutions. Profiling has yet to be carried out to map this in the Indonesian Language and Literature Education Study Program. Therefore, this research aims to profile 21st Century Skills and Information Literacy in Indonesian Language and Literature Education. This type of research is mixed methods research using a Concurrent Embedded Design. The respondents were 30 undergraduate students of Indonesian Language and Literature Education. Methods of data collection using observation, interviews, and questionnaires. The research instruments used were questionnaires, interview guides, and observation sheets. Data were analyzed using the Mann-Whitney U Test. The study's results, namely critical thinking skills and problem-solving, communication and collaboration, creativity and innovation, and information literacy skills, still needed to be higher for most students. Only the Creativity and Innovation Skills skills differed significantly between the upper and lower semesters. The study findings are discussed, followed by a review of the implications for educational institutions, policymakers, and future research.